A escrita em inglês do gênero biodata por meio de colaboração online em turmas numerosas do ensino médio: um estudo de caso - Patricia Melo Muradas (2013)
This research aimed to investigate the pedagogical potential of Google Docs as a tool to support the process of collaborative writing based on a genre orientation. The aim was to understand how this technological tool can favor collaborative writing. In addition, an attempt was made to evaluate the production of the text genre biodata as a recursive process, which includes stages of rough drafts, a first version, revisions and a second version. The study was conducted in a large high school class of a mainstream school in Belo Horizonte, in the state of Minas Gerais. The didactic procedures that underpin the teaching of writing as a process in the Google Docs platform emphasized the study of the textual plan of a biodata, ie, its content, its discursive-multimodal and its lexical-grammatical aspects. Data collection was initially carried out by having participants in the study respond to two questionnaires. The first, submitted to the respondents before starting to produce the text, set out to obtain the students perceptions about writing in English in their learning activities. The second sought to investigate if and what changes occurred in the respondents' perceptions after having an experience of writing collaboratively in English as a process in an online environment. Thereafter, the biodatas produced by the participants were also analyzed (first and second versions). Finally, the collaborative processes that occurred prior to writing the second version were also observed. Based on the data analyzed, it was found that Google Docs is an important pedagogical tool for writing a biodata in English collaboratively in an online environment. It was also possible to confirm that writing production anchored on the recursive process prompts monitoring and interaction among learners involved.